Efektivitas Tingkat Literasi Keuangan, Kepercayaan dan Kualitas Pelayanan terhadap Minat Menabung di Bank Syariah - Sriyono; Siska Putri Utami; Tiara Nur Mediana Faradilah; Safira Ariskiya; Sofiyatus Zahro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Due to a lack of knowledge and exposure to sharia banks, people tend to think that saving at conventional banks and sharia banks is the same. The decline in people's interest in saving in sharia banking is also influenced by the increasingly widespread use of conventional banking compared to sharia banking. Financial literacy does not have a significant effect on interest in saving at Islamic banks. Trust has a positive and significant effect on interest in saving in Islamic banks. The influence of service quality on the research results shows that the service quality variable has a significant influence on people's interest in saving at Sharia Banks. Financial literacy does not have a significant effect on interest in saving at Sharia Banks. Trust has a positive impact on interest in saving at Sharia Banks. The quality of this service has a big influence on people's interest in saving at Sharia Banks